Methods of management of bottom sediments from selected water reservoirs – a literature review - Tomczyk-Wydrych, Ilona; Świercz, Anna (Geologos, 2021)
Sediment accumulation is a process that is typical of all types of water reservoirs. The rate and pattern of such accumulation are related to processes taking place in catchments that produce the sediments and to those within reservoirs that determine the percentage of the inflowing load that is trapped and where it is deposited. To keep reservoirs in working order requires desilting and managing of such bottom sediments once they are removed. The choice of strategy for sediment management depends on chemical and physical properties which result from both natural and anthropogenic processes. To varying degrees, these sediments may be contaminated with chemical compounds, especially trace metals. Therefore, research is needed in order to assess the quality of sediments, which will allow to opt for the proper management strategy. Based on an analysis of the available literature, the possibility of using sediments from reservoirs has been determined, using quality criteria and in accordance with applicable law and regulations.